THE EFFECT OF GINGER AND TURMERIC ON PRIMARY DYSMENORRHEA - Masyithah Ridhati; Mukhoirotin Mukhoirotin (Jurnal Keperawatan Muhammadiyah, 2023)
Objective: To determine the difference in the effect of giving ginger and turmeric on dysmenorrhea in adolescents at the Hurun Inn Dormitory of Darul 'Ulum Jombang Islamic Boarding School that met the research criteria.Methods: The research design used was Quasy Experiment with the two-group pre-posttest design approach. The population in this study were 70 respondents with a sample of 24 respondents obtained by purposive sampling technique. The instrument for measuring pain was using the Numeric Rating Scale (NRS), the data were analyzed using statistical test the Repeated Anova continued with post hoc paired wise comparison and Independent T-Test with a significant level of 5% (âºÂ â‰¤ 0.05).Results: The results showed that there was an effect of giving ginger and turmeric on dysmenorrhea with a significant value of p < 0.05 (P < Î±), there was no significant difference in the two groups (2.583Â±1.93 vs 3.333Â±2.35; p > 0.05).Conclusion:Â The administration of ginger and turmeric is effective in reducing dysmenorrhea so that it can be used as an alternative to overcome dysmenorrhea.